2013
DOI: 10.1111/peps.12051
|View full text |Cite
|
Sign up to set email alerts
|

Helpful Today, But Not Tomorrow? Feeling Grateful as a Predictor of Daily Organizational Citizenship Behaviors

Abstract: This research extends the existing theoretical understanding of what predicts organizational citizenship behavior (OCB). Using experience sampling techniques, we examine the within-person relation between OCB and a novel, theoretically relevant predictor: state gratitude. Using 4 independent samples with a total of 210 working adults and 173 undergraduate students, we developed a reliable and valid measure of state gratitude. Drawing upon the moral affect model of gratitude and affective events theory, we cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 88 publications
(150 reference statements)
7
123
0
3
Order By: Relevance
“…We encourage future leadership researchers to continue to explore the role of discrete emotions as they may have unique predictive value. For example, recently, Spence, Brown, Keeping, and Lian (2014) found that gratitude predicted helping behaviors at work above and beyond positive affect.…”
Section: Limitationsmentioning
confidence: 98%
“…We encourage future leadership researchers to continue to explore the role of discrete emotions as they may have unique predictive value. For example, recently, Spence, Brown, Keeping, and Lian (2014) found that gratitude predicted helping behaviors at work above and beyond positive affect.…”
Section: Limitationsmentioning
confidence: 98%
“…Consistent evidence of the positive link between gratitude and prosocial behaviors has accumulated (see meta‐analytic review: Ma et al, ). In the organizational context, when employees feel gratitude at the episodic level, they engage in more prosocial behaviors, such as engaging in more OCBs on that day (Spence, Brown, Keeping, & Lian, ). In the current study, we argue that persistent gratitude may prompt OCB‐I at the individual level, and there are two theories that can help explain this positive relationship.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…We measured receiving help at work using three items from the scale developed by Spence, Brown, Keeping and Lian (2013). CSRs were asked to indicate the extent to which they received help at work that day (1 = "never"; 5 = "always").…”
Section: Receiving Helpmentioning
confidence: 99%